Repair of Acute Patellar Tendon Rupture Augmented with Strong Sutures - Otsubo, Hidenori; Kamiya, Tomoaki; Suzuki, Tomoyuki; Kuroda, Miki; Ikeda, Yasutoshi; Matsumura, Takashi; Yamashita, Toshihiko (The Journal of Knee Surgery, 2017)
Rupture of the patellar tendon is an uncommon injury that requires acute surgical repair to restore the function of the knee. Multiple techniques for repair have been described in the literature. Complications with these repair techniques include rerupture and extensor lag caused by gap formation at the site of repair. Thus, many surgeons have suggested augmenting the standard repair. Several methods of augmentation have been described each with disadvantages. The purpose of this article was to present our case series of six patients with acute patella tendon ruptures treated by a novel procedure using strong sutures. In this method, eight strands of four-strong sutures run within the tendon. At the patellar site, a combination of suture button and figure eight pattern techniques is used, avoiding stress concentration. The optimal tension is applied to each suture, so as the patella might be positioned at the original placement. Then all sutures are secured onto the tibia. Postoperatively with a mean follow-up of 32.7 months (range: 25–48 months), all patients had a stable knee with mean flexion of 143.3 degrees (range: 140–150 degrees) and without any extension lag. With an improvement in the International Knee Documentation Committee score to 86.8 (range: 80–92), the excellent outcome was noted in all patients. The average postoperative Lysholm score was 98.8 (range: 97–100) and the average Kujala score was 95.2 (range: 92–97). All patients recovered to near-normal strength and stability of the patellar tendon as well as restoration of function after the operation. This augmentation technique offers a distinct advantage over previous augmentation methods and materials, and may be especially useful in managing patellar tendon rupture caused by rheumatoid arthritis or other systemic conditions. For these reasons, we recommend this procedure for acute patellar tendon ruptures.
Keywords: patellar tendon rupture; acute; repair; augmentation; strong suture